Analysis Of Digital Archive Management At Institution X: English - Andini Najwa Putri (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research was conducted with the aim of finding out the archive management system, the positive impact of the implementation of digital archives, and the challenges faced in managing digital archives in Institution X. The design of this study uses qualitative research with a case study approach to provide a comprehensive picture. The research sample selection technique uses a non-probability sampling method with a purposive sampling method. The data collection technique is carried out using several methods, namely observation, interviews and documentation. Meanwhile, the data validity technique is carried out using the triangulation method. The results of this study show that the management of digital archives in Institution X is not optimal. The implementation of digital archives in Institution X has a positive impact, such as increased efficiency in document search and collaboration between teams. However, the system also faces obstacles in the form of application inintegration and lack of training. The solution to overcome these obstacles is to develop an integrated digital archive system and carry out periodic training. It is hoped that the results of this study can provide suggestions and inputs related to the management of digital archives for future improvements.